Paths to a World-Class University Lessons from Practices and Experiences - Liu, Nian Cai.; Wang, Qi.; Cheng, Ying.; SpringerLink (Online service) (Rotterdam : SensePublishers, 2011)
Within higher education, world-class universities are regarded as elite research universities and play a critical role in developing human resources and generating new knowledge in the context of a knowledge-based economy. Governments around the world have made the operation of their universities at the cutting edge of intellectual and scientific development their policy priority; and top universities make every effort to compete at this global stage. (3z(BPaths to A World-Class University(3y (Bprovides insights into recent and ongoing experiences of building world-class universities, both at a national level and at an institutional level. It collects fifteen essays, most of which originated from papers presented at (3z(BThe Third International Conference on World-Class Universities(3y(B, held in November 2009 in Shanghai, China, and organised by the Center for World-Class Universities of Shanghai Jiao Tong University. Divided into two parts, the book: - focuses on the role of world-class universities in national systems; and - looks at institutional experiences and lessons in building world-class universities. This book not only represents a contribution to the ongoing discussion on the topic of building world-class universities, but can be seen a continuation of the previous two volumes on this topic - (3z(BWorld-Class Universities and Ranking: Aiming beyond Status(3y (Band (3z(BThe World-Class University as Part of a New Higher Education Paradigm: From Institutional Qualities to Systemic Excellence(3y(B. All three books will be useful reading for students and academics in higher education generally, in addition to policy makers and informed practitioners.s
Keywords: Education; Education, Higher; Education; Higher Education